Global Knowledge Structure of Urban Green Space Research in Hot–Humid Regions (2000–2025): A Bibliometric Analysis - Alhammad, Bader A.; Altwaijri , Ahmad K.; Alhowaish, Abdulkarim K. (Journal of Cultural Analysis and Social Change, 2026)
Urban green spaces (UGS) are widely discussed as contributing to livability and moderating heat stress, especially in hot–humid regions where microclimate challenges are more pronounced. However, research remains distributed across multiple themes without a unified synthesis of its intellectual development. This study uses bibliometric mapping to analyze UGS-related scholarship between 2000 and 2025, identifying dominant clusters, thematic linkages, and publication trends rather than evaluating on-ground performance. A total of 94 peer-reviewed publications indexed in Scopus and Web of Science were analyzed through co-occurrence networks, thematic clustering, and overlay visualization. The analysis indicates four major knowledge groupings: (1) green infrastructure and planning, (2) tropical and hot–humid climate contexts, (3) ecosystem-service-oriented literature, and (4) urban heat island and thermal comfort research. Temporal patterns further suggest a shift from early microclimate-focused studies toward more integrated discussions connecting ecosystem services, modelling, resilience, and planning. The study therefore maps how the field conceptually frames UGS, rather than proving their direct environmental or social outcomes, and may support future empirical work by highlighting where research is thematically expanding.